Ship noise in an urban estuary extends to frequencies used for echolocation by endangered killer whales - Veirs,Scott; Veirs,Val; Wood,Jason D (PeerJ PrePrints, 2015)
Combining calibrated hydrophone measurements with vessel location data from the Automatic Identification System, we estimate underwater sound pressure levels for 1,582 unique ships that transited the core critical habitat of the endangered Southern Resident killer whales during 28 months between March, 2011, and October, 2013. Median received spectrum levels of noise from 2,812 isolated transits are elevated relative to median background levels not only at low frequencies (20-30 dB re 1 microPa2/Hz from 100-1000 Hz), but also at high frequencies (5-13 dB re 1 microPa2/Hz from 10,000-96,000 Hz). Thus, noise received from ships at ranges less than 3 km extends to frequencies used by odontocetes like the Southern Resident orcas for communication and echolocation. Broadband received levels (20-96,000 Hz) near the shoreline in Haro Strait (WA, USA) for the entire ship population were 111 +/- 6 dB re 1 microPa on average. Mean ship speed was 14.4 +/- 4.1 knots. Most ship classes show a linear relationship between received level and speed with a slope near +1 dB/knot. Assuming near-spherical spreading based on a transmission loss experiment, we compute mean broadband source levels for the ship population of 173 +/- 7 dB re 1 microPa @ 1 m without accounting for frequency-dependent absorption, and 178 +/- 13 dB re 1 microPa @ 1 m with absorption. Spectrum, 1/12-octave, and 1/3-octave source levels for the whole population have median values that are comparable to previous measurements and models at most frequencies, but for select studies may be relatively low below 200 Hz and high above 20,000 Hz. Median source spectrum levels (without accounting for absorption) peak near 50 Hz for all 12 ship classes, have a maximum of 159 dB re 1 microPa2/Hz @ 1 m for container ships, and vary between classes by about 25 dB re 1 microPa2/Hz @ 1 m at low frequencies (50 Hz), 13 dB re 1 microPa2/Hz @ 1 m at mid-frequencies (1,000 Hz), and 5 dB re 1 microPa2/Hz @ 1 m at high frequencies (10,000 Hz). Below 200 Hz, the class-specific median spectrum levels bifurcate with large commercial ships grouping as higher power noise sources. Within all ship classes spectrum levels vary more at low frequencies than at high frequencies, and the degree of variability is almost halved for classes that have smaller speed standard deviations.
Keywords: noise; hydrophone; killer whale; orca; odontocete; marine mammal; ship